King-Devick concussion test performs poorly as a screening tool in elite rugby union players: a prospective cohort study of two screening tests versus a clinical reference standard - Fuller, G. W.; Cross, M. J.; Stokes, K. A.; Kemp, S. P. T. (British Journal of Sports Medicine, 2019)
Background: The King-Devick (KD) test is an objective clinical test of eye movements that has been used to screen for concussion. We characterised the accuracy of the KD test and the World Rugby Head Injury Assessment (HIA-1) screening tools as methods of off-field evaluation for concussion after a suspicious head impact event. Methods: A prospective cohort study was performed in elite English rugby union competitions between September 2016 and May 2017. The study population comprised consecutive players identified with a head impact event with the potential to result in concussion. The KD test was administered off-field, alongside the World Rugby HIA-1 screening tool, and the results were compared with the preseason baseline. Accuracy was measured against a reference standard of confirmed concussion, based on the clinical judgement of the team doctor after serial assessments. Results: 145 head injury events requiring off-field medical room screening assessments were included in the primary analysis. The KD test demonstrated a sensitivity of 60% (95% CI 49.0 to 70) and a specificity of 39% (95% CI 26 to 54) in identifying players subsequently diagnosed with concussion. Area under the receiver operating characteristic curve for prolonged KD test times was 0.51 (95% CI 0.41 to 0.61). The World Rugby HIA-1 off-field screening tool sensitivity did not differ significantly from the KD test (sensitivity 75%, 95% CI 66 to 83, P=0.08), but specificity was significantly higher (91%, 95% CI 82 to 97, P<0.001). Although combining the KD test and the World Rugby HIA-1 multimodal screening assessment achieved a significantly higher sensitivity of 93% (95% CI 86% to 97%), there was a significantly lower specificity of 33% (95% CI 21% to 48%), compared with the HIA-1 test alone. Conclusions: The KD test demonstrated limited accuracy as a stand-alone remove-from-play sideline screening test for concussion. As expected with the addition of any parallel test, combination of the KD test with the HIA-1 off-field screening tool provided improved sensitivity in identifying concussion, but at the expense of markedly lower specificity. These results suggest that it is unlikely that the KD test will be incorporated into multimodal off-field screening assessments for concussion at the present time.